From Nanostructures to Nanosensing Applications - D'amico, A (IOS Press, 2014)
Nanoscience and Nanotechnologies are developing at a very fast pace. It is then important to provide young and even expert scientists with the possibility of reviewing and updating some of the most significant features of nanostructures for a better understanding of their scientific foundations in order to put a firm basis for future developments.